A doctor at the Real Felipe fortress: Dr. José Pezet y Monel prisoner in Callao (1823-1825) - Castro Olivas, Jorge Luis (2022)
This paper explains why the creole doctor Jose Pezet y Monel was imprisoned at the Real Felipe Fortress in Callao. Pezet was a modern and liberal intellectual who early identified himself with the insurgent cause. His support for the president José de la Riva Agüero and a series of unfortunate events precipitated his death. We review his will signed in Callao on August 5, 1825.